2019
DOI: 10.1051/0004-6361/201936333
|View full text |Cite
|
Sign up to set email alerts
|

The impact of thermal winds on the outburst lightcurves of black hole X-ray binaries

Abstract: Context. The observed signatures of winds from X-ray binaries are broadly consistent with thermal winds, driven by X-ray irradiation of the outer accretion disc. Thermal winds produce mass outflow rates that can exceed the accretion rate in the disc. Aims. We aim to study the impact of thermal wind mass loss on the stability and lightcurves of black hole X-ray binaries subject to the thermal-viscous instability, which drives their outbursts. Strong mass loss could shut off outbursts early, as proposed for the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 63 publications
2
22
0
Order By: Relevance
“…Evidence for this type of behaviour has been (i) to an extent, observed previously in BH-LMXBs XTEJ1817−330 and XTEJ1859+226, and (ii) recently predicted by Dubus et al (2019), who consider the impact a thermally-driven wind would have on BH-LMXB light-curves, in the context of the disc-instability model. By fitting an irradiated disc model to broadband SEDs observed throughout the 2006 outburst of XTE J1817−330, Gierliński et al (2009) found that while soft state observations were consistent with a near constant fraction of bolometric X-ray luminosity being reprocessed in the outer disc, the reprocessed fraction increased by a factor ∼ 6 as the source transitioned into the hard state.…”
Section: −3supporting
confidence: 53%
See 3 more Smart Citations
“…Evidence for this type of behaviour has been (i) to an extent, observed previously in BH-LMXBs XTEJ1817−330 and XTEJ1859+226, and (ii) recently predicted by Dubus et al (2019), who consider the impact a thermally-driven wind would have on BH-LMXB light-curves, in the context of the disc-instability model. By fitting an irradiated disc model to broadband SEDs observed throughout the 2006 outburst of XTE J1817−330, Gierliński et al (2009) found that while soft state observations were consistent with a near constant fraction of bolometric X-ray luminosity being reprocessed in the outer disc, the reprocessed fraction increased by a factor ∼ 6 as the source transitioned into the hard state.…”
Section: −3supporting
confidence: 53%
“…While this thermal wind, predicted to be present in both the hard and soft accretion states, may not be a dominant mechanism for mass loss in this system, it does play an important role in the accretion process in terms of irradiating the disc. Using this wind as a medium in which to scatter X-rays back onto the disc, we are able to reproduce some of the features, independently predicted to be present (e.g., Kimura & Done 2019;Dubus et al 2019), in our computed C(t) outburst profiles (see Section 4.1). Such features include the peaks/drops in C occurring during accretion state transitions and complex (day-week timescale) variability.…”
Section: The Role the Wind Plays During Outburst Cycles In Gx339−4mentioning
confidence: 69%
See 2 more Smart Citations
“…The disc must therefore be warped, or the central irradiating source must be extended, or both. The source extension can be either due to the formation of a hot corona or to the existence of thermal winds as considered by Dubus et al (2019) that scatter the X-rays back to the disk. The problem then becomes extremely complex, and depends on many unknown parameters such as the shape of the disk or the source extent; Dubus et al (1999)…”
Section: Irradiation Of the Accretion Disc 441 Irradiation By The mentioning
confidence: 99%